(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Idiopathic pulmonary fibrosis is a pathological process in the lungs characterized by refractory to therapy and high mortality rates, it is a heterogeneous group of disorders with progressive and irreversible destruction of the lung architectonics due to scarring, which ultimately leads to organ dysfunction, gas exchange disorders and death due to respiratory failure [D.V. Bestaev, 2014]. The article presents a review of the literature on modern concepts of idiopathic pulmonary fibrosis.